Analisis Kelemahan Organisasi Serikat Pekerja dalam Meningkatkan Kesejahteraan Anggota dan Keluarga - Bahtiar, Ade; Isra, Muhammad; Pasaribu, Lusia iti Sumarni; Wijatmoko, Agus; Albana, Yusup (Journal of Industrial Relations Studies, 2025)
The weaknesses of labor unions, both from internal factors such as limited resources and weak leadership, and external factors such as government intervention and company pressure, significantly impact the welfare of their members and their families. This study employs a normative juridical method with a statutory approach, including Law No. 21 of 2000 and Law No. 13 of 2003, as well as agency theory and stakeholder theory. The findings reveal that these weaknesses lead to decreased income, loss of social security, and limited access to welfare programs. Solutions include strengthening the organization's internal capacity, increasing member participation, and fostering collaboration with companies and the government